Enseñando Sabroso: Cuidado, Salud y Capitalismo en el rol del Psicoterapeuta (Hilo Analítico, 2024)
Understanding the process of change and historical progress in Colombia, two critics and a proposal are presented regarding the work of the health psychologist and psychotherapists in the framework of the teaching-learning processes, the medicalizing role and the critical-historical-decolonial perspective to the problem of the inclusion of psychology as an ethic of capitalism.